INTEGRATIVE MUSYRIF STRATEGIES IN CULTIVATING RELIGIOUS CULTURE AT KH MAS MANSUR UMS STUDENT PESANTREN - Mukti, Bagas Ali; Mustofa, Triono Ali (International Journal of Cultural and Social Science, 2026)
This study aims to examine musyrif strategies in cultivating religious culture, the implementation of these strategies, and the barriers encountered at KH Mas Mansur UMS Student Pesantren. This study employed a qualitative case study approach using in-depth interviews, observation, and documentation involving the Board of Caretakers, ISO administrators, and student residents. The findings reveal three main musyrif strategies: exemplary conduct (uswah hasanah), humanistic personal approaches, and structured habituation through routine religious activities. The implementation of these strategies was carried out through planning, implementation, monitoring, and evaluation processes integrated into students’ daily life within the pesantren environment. The study also identified two major categories of barriers: internal barriers, including low initial awareness, parental coercion, laziness, and burnout; and external barriers, including peer influence, inconsistent role modeling among administrators, unclear sanction systems, and limited socialization of regulations. This study contributes an integrative musyrif strategy model that combines exemplary conduct, personal approaches, and structured habituation in fostering religious culture within a university student pesantren context.